Resistome Analysis of Campylobacter jejuni Strains Isolated from Human Stool and Primary Sterile Samples in Croatia - Silvija Šoprek; Sanja Duvnjak; Gordan Kompes; Luka Jurinović; Arjana Tambić Andrašević (Microorganisms, 2022)
Campylobacteriosis represents a global health challenge due to continuously increasing trends of antimicrobial resistance in Campylobacter jejuni. C. jejuni can sometimes cause life-threatening and severe systematic infections (bacteremia, meningitis, and other extraintestinal infections) with very few antibiotics left as treatment options. Bearing in mind that C. jejuni is the predominant species in humans, in this paper, we present a study of the C. jejuni differences in antimicrobial resistance and genotype distribution between strains isolated from stool and primary sterile sites. We compared the genomic data obtained through whole genome sequencing (WGS) and phenotypic susceptibility data of C. jejuni strains. Once antimicrobial susceptibility testing of C. jejuni strains was carried out by the broth microdilution method for six of interest, results were compared to the identified genotypic determinants derived from WGS. The high rate of resistance to fluoroquinolones presented in this study is in accordance with national surveillance data. The proportion of strains with acquired resistance was 71% for ciprofloxacin and 20% for tetracycline. When invasive isolates were analysed separately, 40% exhibited MIC values of ciprofloxacin higher than the ECOFFs, suggesting a lower flouroquinolone resistance rate in invasive isolates. All isolates demonstrated wilde-type phenotype for chloramphenicol, erythromycin, gentamicin, and ertapenem. A special focus and review in this study was performed on a group of C.jejuni strains found in primary sterile samples. Apart from demonstrating a lower resistance rate, these isolates seem genetically more uniform, showing epidemiologically more homogenous patterns, which cluster to several clonal complexes, with CC49 being the most represented clonal complex.